2013
DOI: 10.1016/j.biopsych.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Spontaneous Attention to Social Scenes in 6-Month-Old Infants Later Diagnosed with Autism Spectrum Disorders

Abstract: Background The ability to spontaneously attend to the social overtures and activities of others is essential for the development of social cognition and communication. This ability is critically impaired in toddlers with autism spectrum disorders (ASD); however, it is not clear if prodromal symptoms in this area are already present in the first year of life of those affected by the disorder. Methods To examine whether 6-month-old infants later diagnosed with ASD exhibit atypical spontaneous social monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
356
3
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(419 citation statements)
references
References 52 publications
33
356
3
13
Order By: Relevance
“…To our knowledge, only a few studies quantitatively compare attention to stimuli of different social complexity in autism spectrum disorders in real-life settings (e.g., by analyzing retrospective home videos). Note that our results agree with the recent eye-tracking studies conducted in semi-naturalistic settings by Chawarska et al [54] and Shic et al [55]. Both studies reported that children with ASD looked proportionally less time at an actor's face, when the actor was speaking, than TD children and children with developmental delays.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, only a few studies quantitatively compare attention to stimuli of different social complexity in autism spectrum disorders in real-life settings (e.g., by analyzing retrospective home videos). Note that our results agree with the recent eye-tracking studies conducted in semi-naturalistic settings by Chawarska et al [54] and Shic et al [55]. Both studies reported that children with ASD looked proportionally less time at an actor's face, when the actor was speaking, than TD children and children with developmental delays.…”
Section: Discussionsupporting
confidence: 93%
“…They observe that people with autism orient to social sound less than to non-social sounds. Recently, Chawarska et al [54] conducted a semi-naturalistic eye-tracking study that involved children with ASD (n = 54, mean age = 1.8 years), TD children (n = 48, mean age = 1.7 years) and children with developmental delays (n = 20, mean age = 1.7 years), matched on verbal and non-verbal mental age. Chawarska et al compared the gaze behaviours towards faces.…”
Section: Introductionmentioning
confidence: 99%
“…In the developmental trajectory of social cognition visual attention is given to faces very soon after birth, with specific attention paid to the eye region; and later in infancy at around 6-9 months a preference for looking at faces within multiple object arrays or animated scenes develops (Johnson, Dziurawiec, Ellis, & Morton, 1991;Farroni, Csibra, Simion, & Johnson, 2002;Gliga, Elsabbagh, Andravizou, & Johnson, 2009;Frank, Vul, & Johnson, 2009); for review see . This trajectory is altered from 2 to 12 months in children who go on to receive a diagnosis of ASD, which suggests that gaze behaviour may be one of the earliest markers of atypical social cognition (Young, Merin, Rogers, & Ozonoff, 2009;Ozonoff et al, 2010;Chawarska, Macari, & Shic, 2012;Jones & Klin, 2013;Chawarska, Macari, & Shic, 2013;Wass et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, one interpretation of existing findings is that infants who later receive a diagnosis of ASD are more easily distracted by colorful objects in the background of a scene, or by specific stimulus properties such as audiovisual contingencies (Chawarska, Macari, & Shic, 2013; Klin, Lin, Gorrindo, Ramsay, & Jones, 2009). Thus, conflicting results from the literature on early signs of ASD may be partially explained by differences in stimulus and task design (Falck‐Ytter, Bolte, & Gredeback, 2013; Jones, Gliga, Bedford, Charman, & Johnson, 2014).…”
mentioning
confidence: 99%